Effect of Residual and Intercycle Ice Accretions on Airfoil Performance - Broeren, Andy P.; Bragg, Michael B. (2002)
This report describes the results of an experimental study designed to characterize and evaluate the aerodynamic performance penalties of residual and intercycle ice accretions that result from the cyclic operation of a typical aircraft deicing system. Icing wind tunnel tests were carried out on a 36 inch chord NACA 23012 airfoil section equipped with a pneumatic deicer for several different cloud conditions modeled after FAR 25 Appendix C. Results from the icing tests showed that the intercycle ice accretions were much more severe in terms of size and shape than the residual ice accretions. Molds of selected intercycle ice shapes were made and converted to castings that were attached to the leading edge of a 36 inch chord NACA 23012 airfoil model for aerodynamic testing. The aerodynamic testing revealed that the intercycle ice shapes caused a significant performance degradation. Maximum lift coefficients were typically reduced about 60% from 1.8 (clean) to 0.7 (iced) and stall angles were reduced from 17 deg. (clean) to 9 deg. (iced). Changes in the Reynolds number (from 2.0 x 106 to 10.5 x 106) and Mach number (from 0.10 to 0.28) did not significantly affect the iced-airfoil performance coefficients.